Salinity‐Difference‐Driven Power Generation by a Hybrid Capacitive Approach. Issue 2 (11th December 2017) - Zhan, Fei; Wang, Gang; Wu, Tingting; Dong, Qiang; Meng, Yulan; Wang, Jianren; Qiu, Jieshan
Abstract: The extraction of salinity gradient energy remains a challenging task. In this paper, we propose a new method for the extraction of salinity gradient energy by using a hybrid capacitor, which consists of a battery electrode and a porous carbon electrode. The potentials of the Na4 Mn9 O18 (NMO) and activated carbon (AC) electrodes show opposite dependencies on salt concentration, so that as fresh water and salt water flow alternately through the hybrid capacitor, the voltage difference between the electrodes can be increased by 110 mV. Our results demonstrate the viability of this new method to harvest salinity gradient energy without using membranes or precious metals. Abstract : Hybrid capacitive mixing : A hybrid capacitor that consists of a battery electrode (Na4 Mn9 O18 ) and an activated carbon electrode can be used to extract renewable energy from a salinity difference. A four‐step energy‐generation cycle that uses this hybrid capacitor is realized. The open‐circuit voltage increase of the capacitor is 110 mV.